Carbohydrate and nutrient composition of corn stover from three southeastern USA locations. (February 2016) - Mourtzinis, Spyridon; Cantrell, Keri B.; Arriaga, Francisco J.; Balkcom, Kipling S.; Novak, Jeff M.; Frederick, James R.; Karlen, Douglas L.
Abstract: Corn ( Zea mays L.) stover has been identified as an important feedstock for bioenergy and bio-product production. Our objective was to quantify nutrient removal, carbohydrate composition, theoretical ethanol yield (TEY) for various stover fractions. In 2009, 2010, and 2011, whole-plant samples were collected from one field study in South Carolina (SC) and two in Alabama (AL). Soils at the SC site were classified as a Coxville/Rains-Goldboro-Lynchburg association, while those in AL were either Compass or Decatur. Plants were collected from two 1-m row segments, ears were removed and shelled. A portion of the remaining stalks were dried and ground to represent whole-plant stover. The remaining stalks were fractionated into stalk and leaf biomass from below the ear (bottom), stalk and leaf biomass from above the ear (top), cobs, and grain. A fifth sample representing "above-ear" biomass that might be collected mechanically was calculated using the weight ratios of the top and cob fractions. Carbohydrate and nutrient concentrations were estimated using near-infrared spectroscopy (NIRS) and TEY was calculated. The distribution of carbohydrates, nutrients, and TEY varied significantly among the corn stover fraction and research locations. This indicates that site-specific sampling and analysis should be used to optimize bioenergy and bio-product utilization of corn stover. However, at every location, the above-ear stover fractions were most desirable for cellulosic ethanol production. Furthermore, harvesting only above-ear stover fractions would reduce nutrient removal by 24–61% when compared to harvesting all stover biomass. Highlights: We quantify nutrient and carbohydrate composition, and theoretical ethanol yield (TEY) for various stover fractions. We report results from a nine site-years study (3 years, 3 locations) across the southeastern US. The distribution of carbohydrates, nutrients, and TEY varied significantly among the corn stover fraction and research locations. The above-ear stover fractions were most appropriate for cellulosic ethanol production. Harvesting only above-ear stover fractions would reduce nutrient removal by 24–61% compared to harvesting whole plant biomass.